HUBUNGAN STATUS SOSIAL EKONOMI DENGAN PRAKTEK PERILAKU MENJAGA KEBERSIHAN GIGI DAN MULUT PADA MASYARAKAT - Ni Made Yuliana; Jeana Lydia Maramis; Yenny Lisbeth Siahaan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
Socioeconomic status in terms of employment, income or expenditure and education. One of the factors causing dental and oral health problems is the behavior of people who are less aware of the importance of maintaining healthy teeth and mouth. The purpose of this study was to determine the relationship between socioeconomic status and the practice of maintaining oral hygiene in the community of the Molas III Neighborhood, Bunaken District, Manado City. This type of research uses an analytic survey research method with a cross sectional design. The sampling technique is Accidental Sampling using a mixture of inclusion and exclusion. The sample used was 40 people from the community in June 2022 in the Molas III Village, Bunaken District, Manado City. Research instruments in the form of questionnaires and checklist sheets. The data obtained is tabulated and presented in the form of a percentage distribution table while the Chi-Square test is used to determine the relationship. Thus the results of the Chi Square test value p = 0.000 (< ? 0.05) and r count = 15.63 > r table = 3.84). H0 is rejected and H1 is accepted. There is a relationship between socioeconomic status and dental and oral hygiene behavior.